2015
DOI: 10.1680/macr.14.00213
|View full text |Cite
|
Sign up to set email alerts
|

Modulus of elasticity of recycled aggregate concrete

Abstract: Various empirical equations have previously been suggested for estimating the modulus of elasticity of concrete from its compressive strength. In addition, a considerable number of practical and universal equations have been proposed for predicting the modulus of elasticity when the product includes coarse aggregates and various types of mineral additions. However, such equations are not applicable to the whole data for recycled aggregate concrete because its mechanical properties depend greatly on both the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Different authors (31,32) analysed the relationship between the cube compressive strength (f cu ) 0 10 20 30 40 50 60 70 80 90 …”
Section: Compressive Strength (F C )mentioning
confidence: 99%
“…Different authors (31,32) analysed the relationship between the cube compressive strength (f cu ) 0 10 20 30 40 50 60 70 80 90 …”
Section: Compressive Strength (F C )mentioning
confidence: 99%
“…The results show that the compressive and splitting tensile strength of RAC depends on the mix proportions [18]. Noguchi et al used statistical data from 1,300 tests conducted in Japan and South Korea from 1980 to 2012 to analyze the relationship between compressive strength and elastic modulus [19]. In the triaxial static compression performance of RAC, Chen et al found that the aging time and the lateral constraint have great influence on the peak strain and the elastic modulus of the RAC [20].…”
Section: State Of the Artmentioning
confidence: 99%
“…From the 43 publications of a review nature, two groups were created based on the origin of the information & group 1: established organisations, codes and proposed specifications (as listed in Table 1) & group 2: individual researchers (Agrela et al, 2013;Ajdukiewicz, 2005;Balazs et al, 2008;Behera et al, 2014;de Brito and Alves, 2010;de Brito and Robles, 2010;Dhir et al, 2011;Franklin and Gumede, 2014;Kukadia et al, 2014;Li, 2008aLi, , 2008bMarinkovic et al, 2012;McNeil and Kang, 2013;Nixon, 1978;Park et al, 2015;Poon et al, 2003;Ramachandran, 1981;Rao et al, 2007;Safiuddin et al 2013;Safiuddin et al, 2011;Xiao et al, 2006aXiao et al, , 2012aXiao et al, , 2012b.…”
Section: Overview Of the Literaturementioning
confidence: 99%